(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article investigates that the line goes between diary fiction and letter fiction and how these two genres differ from each other. The closest consensus from the scholars discussed here is that letter fiction often is intensely focused on the existence of a reader, while diary fiction in its purest form is focused on the isolation of the self, and the self-consciousness in writing something that is directed at this self rather than recipients that cannot be reached with the spoken word.